Realizing collective action in agency-constrained contexts: the case of the Community Fish Refuges in Cambodia - Baldivieso Soruco, C. R.; de Silva, Sanjiv; Gleich, P.; Yan, Y.; Dubois, Mark; Sieber, S.; Bonatti, M. (Frontiers Media, 2025)
In rural Cambodia, inland freshwater and rice field fisheries are key sources of income, animal protein, and important ecosystem services. As the flood pulse in the Tonlé Sap floodplain recedes post-monsoon, leaving rice fields and local water bodies dry, Community Fish Refuges (CFRs) offer a promising path to sustain dry season fish stocks, aquatic biodiversity, and secure water for agriculture and husbandry. Their sustained physical integrity and productivity as multiple-use systems hinge on communities’ ability to manage these systems collectively. To explore whether the studied communities have been able to respond to the challenge of collectively governing CFR, we investigate two CFR sites that were established in 2016 by local and international organizations alongside State authorities. Our aim is to investigate two key aspects: 1) the presence, extent, and efficacy of community-level collective action (CA) for managing CFRs; and 2) the factors that either facilitate or inhibit CA regarding CFRs. We conducted a qualitative case study between March and May 2023 at two sites in Kampong Thom Province. These were selected because while they have similar ecological features, they show different management results according to the implementing international organization WorldFish. This paper delves into a process guided by external agents seeking to reshape local behavior and existing institutional frameworks. Results show how centralized power structures and entrenched rural patronage politics in villages limit villagers’ participation and agency in CFRs management. Villagers encounter constraints hindering their capacity to instigate change, prompting a re-evaluation of the CFR Committee’s composition and operation to ensure broader legitimacy among actors. While emphasizing extended project funding and informed external intervention strategies, the study underscores doubts about short-term CA feasibility. It highlights the critical influence of contextual factors and policymakers’ assumptions in achieving effective collective governance. Structural factors and the deeply human process of pulling together a plurality of stakeholders pose challenges to establishing community-based projects prioritizing diverse voices.